THE UNDAGI LEXICON IN THE MANUFACTURE OF RESIDENTIAL HOUSES BASED ON ASTA KOSALA KOSALI CONCEPT IN DENPASAR - Made Sani Damayanthi Muliawan (RETORIKA: Jurnal Ilmu Bahasa, 2017)
The title of this research is The ‘Undagi’ lexicon in the manufacture of residential houses based on asta kosala kosali concept in Denpasar. The aims of this research is to inventory the diversity of vocabulary of undagi’s lexicon in making a house based on asta kosala kosali concept with ecological dimension so that the young generation can know and preserve it well. The theory applied for this research is ecolinguistic theory proposed by Bang and Door (1993). This theory are combines biological dimension, ideological and sociological dimension in the languages. This research is descriptive qualitative. Technique of data collecting is done by applying listening method and speaking method. The listening method is done by using interview technique and the speaking method by using face to face method. The result of the research shows that the diversity of vocabulary of undagis’s lexicon in making a house based on asta kosala kosali concept are found sixty seven lexicons categorized as nouns and thirteen lexicons categorized as verb. In addition to word class categorization, in this study also obtained the word forms of each lexicon in the form of a single form of the word base and derivative form of the form of compound words. Each lexicon also has a semantic meaning and shows the social praxis dimension of ideological, sociological and biological dimensions. Key words: Undagi, asta kosala kosali, the social praxis dimension